Efecto de diferentes niveles de lignocelulosa sobre la integridad de la mucosa intestinal en cobayos - Rodríguez Tacuri, Jonathan David (2024)
Plant lignocellulose, which is found in the cell walls of plants, enhances digestibility and intestinal health in guinea pigs, as well as improving fermentation and fatty acid production. It also acts as a substrate for the intestinal microflora, which contributes to maintaining a balance in the digestive tract. As a result of this study, different levels of lignocellulose were included in the diets of guinea pigs in order to assess their effects on the integrity of their intestinal mucosa. Thirty-two type A1 guinea pigs were randomly distributed in four treatments (0, 3, 8, 8, 12% lignocellulose inclusion) and with eight replicates per treatment for 15 days, after which they were sacrificed to obtain histological samples from the small intestine (jejunum). As a result of staining with hematoxylin and eosin, we were able to determine the following parameters: the villus length, the crypt depth, the ratio (the ratio between the villus length and crypt depth), the epithelium height, and the muscular tunica width. Accordingly, high levels of lignocellulose inclusion led to an improvement in villus length and crypt depth, suggesting that high levels of lignified fiber promote intestinal mucosal development and digestive health.